Bis(3-bromomethyl-2-methoxy-1-naphthyl)methane - Luo, Jie-Wei (International Union of Crystallography, 2008)
The title compound, C(25)H(22)Br(2)O(2), crystallizes with two molecules in the asymmetric unit. In each independent molecule, the two naphthalene ring systems are nearly perpendicular to one another, with dihedral angles of 85.6 (1) and 86.2 (1)°. The crystal structure is stabilized by C—H⋯π interactions, and inter- and intramolecular C—H⋯O and C—H⋯Br hydrogen bonds.